Implementasi Metode ARAS dan Metode Pembobotan ROC untuk Pendukung Keputusan pada Seleksi Penerimaan Karyawan Baru - Arini, Wulan; Sitepu, Yanti Peronika Br; Dewani, Dewani; Fitriani, Nopita; Sembiring, David JM; Ginting, Raheliya Br (Journal Global Technology Computer, 2025)
Employees are one of the most important assets in a company. Their crucial role extends beyond carrying out daily tasks, but also through contributing ideas, innovations, and solutions that can help the company grow. Problems in the recruitment process for new employees often arise due to the large number of applicants with diverse backgrounds, abilities, and experiences. If this problem is not resolved, companies could potentially recruit employees who do not meet the required qualifications. One solution is to implement a Decision Support System (DSS). A DSS is a computer-based system designed to assist decision-makers in solving semi-structured or unstructured problems. In its implementation, a DSS can be integrated with the Additive Ratio Assessment (ARAS) method. To ensure accuracy in the ARAS calculation process, appropriate criteria weighting is required. One such weighting method is Rank Order Centroid (ROC). The purpose of this study is to implement a combination of the ROC and ARAS weighting methods to build a decision support system that can assist companies in selecting new employees who meet predetermined criteria. The combination of the ROC and ARAS methods can be an appropriate solution to overcome the problem of subjectivity, accelerate the selection process, and improve the accuracy of decision-making in hiring new employees. The process obtained a score of 1.000 on A6, indicating that the new employee was selected in the new employee selection process.